2009
DOI: 10.1185/03007990903138416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propionyl-l-carnitine, l-arginine and nicotinic acid on the efficacy of vardenafil in the treatment of erectile dysfunction in diabetes

Abstract: Although there was a small number of subjects in this study the data suggest that the test formulation may improve the endothelial situation in diabetes. The test formulation together with vardenafil was better than the 5PDE inhibitor alone, but further studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Phosphodiesterase type 5 inhibitors, a pharmaceutical agent with anti-oxidant properties, are the first-line treatment option for ED, although the efficacy is lower compared to the general ED population284647. Numerous prospective studies have reported that patients with ED who have long-term intake of folic acid and vitamin B 12 can reduce the blood concentration of HCy and delay the onset of HHCy263148.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphodiesterase type 5 inhibitors, a pharmaceutical agent with anti-oxidant properties, are the first-line treatment option for ED, although the efficacy is lower compared to the general ED population284647. Numerous prospective studies have reported that patients with ED who have long-term intake of folic acid and vitamin B 12 can reduce the blood concentration of HCy and delay the onset of HHCy263148.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials demonstrate that PLC enhances the international index of erectile function scores in diabetic patients treated with sildefanil or verdenafil [92][93][94]. In a preliminary report, Gasbarrini et al [95] have investigated the effects of PLC topical irrigation in distal ulcerative colitis and reported significant improvements in histological features.…”
Section: Other Effectsmentioning
confidence: 99%
“…Other combinations that have been shown to salvage PDE5-Is nonresponders include PDE5-Is and either propionyl L-carnitine [86,87], vitamin E [88], melanocortin receptor agonist [89], losartan [90], pioglitazone [91], quinapril and atorvastatin [92], pentoxifylline [93], vitamin B6, and folic acid [94], or continuous positive airway pressure [95].…”
Section: Combination Of Phosphodiesterase 5 Inhibitors Plus Systemic mentioning
confidence: 99%